2013
DOI: 10.1002/hep.26108
|View full text |Cite
|
Sign up to set email alerts
|

Tumor progression locus 2/Cot is required for activation of extracellular regulated kinase in liver injury and toll-like receptor-induced TIMP-1 gene transcription in hepatic stellate cells in mice

Abstract: Toll‐like receptors (TLRs) function as key regulators of liver fibrosis and are able to modulate the fibrogenic actions of nonparenchymal liver cells. The fibrogenic signaling events downstream of TLRs on Kupffer cells (KCs) and hepatic stellate cells (HSCs) are poorly defined. Here, we describe the MAP3K tumor progression locus 2 (Tpl2) as being important for the activation of extracellular regulated kinase (ERK) signaling in KCs and HSCs responding to stimulation of TLR4 and TLR9. KCs lacking Tpl2 display de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 42 publications
(56 reference statements)
1
33
0
1
Order By: Relevance
“…20,21 Map3k8 plays a unique role in the production of inflammatory mediators in vivo, 14,19,22 modifying the activation state of macrophages, monocytes, astrocytes, dendritic cells, stellate cells, myofibroblasts, and plasma cells, and no other protein can replace Map3k8 in this role. 16,18,[23][24][25][26][27][28][29] We show here that, in atherogenic conditions, Map3k8 is required to maintain the number of monocytes, by limiting apoptosis. Furthermore, the strong expression of CCR2 on Ly6C high monocytes and the firm adhesion of leukocytes to arterioles and venules in vivo are dependent on Map3k8.…”
Section: Ly6cmentioning
confidence: 59%
“…20,21 Map3k8 plays a unique role in the production of inflammatory mediators in vivo, 14,19,22 modifying the activation state of macrophages, monocytes, astrocytes, dendritic cells, stellate cells, myofibroblasts, and plasma cells, and no other protein can replace Map3k8 in this role. 16,18,[23][24][25][26][27][28][29] We show here that, in atherogenic conditions, Map3k8 is required to maintain the number of monocytes, by limiting apoptosis. Furthermore, the strong expression of CCR2 on Ly6C high monocytes and the firm adhesion of leukocytes to arterioles and venules in vivo are dependent on Map3k8.…”
Section: Ly6cmentioning
confidence: 59%
“…The dissociated and activated Cot/tpl2 stimulates MKK1/2 and consequently Erk1/2 (24 -26), and it is subsequently rapidly degraded through the proteasome pathway (27,28). Cot/tpl2 is the only MAP3K to activate the Erk1/2 pathway in response to both TLR activation and IL-1 or TNF␣ stimulation (29,30) in different cell types, including macrophages, epithelial, and stellate cells (25,29,31). Moreover, Cot/tpl2 can also activate the MAP kinases JNK and p38␣ in certain conditions, in a cell typeand stimulus-specific manner (22,30).…”
mentioning
confidence: 99%
“…The physiological role of TPL2 in signal transduction has largely been explored downstream of Toll-like and TNF receptors in macrophages, dendritic, and hepatic stellate cells (10)(11)(12). These studies have shown that TPL2 ablation ameliorates ERK activation and renders macrophages defective in the production of TNF and other proinflammatory molecules (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the intracellular signaling pathways that mediate the pathogenic functions of iNKT cells remain poorly defined. TPL2 is an MAP3 kinase with an obligatory role in signal transduction on the MEK/ERK axis downstream of receptors involved in innate immunity, including Toll-like (8) and TNF family receptors (9), thereby affecting the production of mediators of inflammation such as TNF, IL-6, cyclooxygenase-2, and TIMP-1 (10)(11)(12). As a result, TPL2 ablation in mice ameliorates the severity of various inflammatory pathologies including LPS-induced endotoxic shock (10), inflammatory bowel disease (13), and the onset and progression of experimental autoimmune encephalomyelitis (14,15).…”
Section: /2mentioning
confidence: 99%